Floristic composition of the Polylepis Yauyinazo and Chaqsii-Chaqsii forests, Nor Yauyos-Cochas Landscape Reserve, Lima - Trinidad, Huber (2016)
Polylepis (Rosaceae) forests are part of the natural vegetation of the Andes between 3500 and 5000 m altitude, usually restricted to rocky slopes and ravines and becoming important ecosystems. During 2008-2010 were made specimens collections in the Yauyinazo and Chaqsii-Chaqsii Polylepis forest into Reserva Paisajística Nor Yauyos-Cochas in two seasons (wet and dry). We present, the vascular flora and seasonal variation the Yauyinazo and Chaqsii-Chaqsii forests. Was registered 282 species in two forests, belonging 170 genera and 62 families, the Asteraceae and Poaceae families were the most diverse. Herbaceous and shrub plants were the most diverse with 71.6% and 17.4% respectively. In Yauyinazo forest were registered 232 species belonging 153 genera and 58 families and in the Chaqsii-Chaqsii forest 213 species belonging 137 genera and 56 families. We report 41 species endemic and 17 threatened flora species, demonstrating the importance of Polylepis forests as habitat for these species.